Accuracy of staging of oral squamous cell carcinoma of the tongue: should incisional biopsy be done before or after magnetic resonance imaging?. Issue 3 (April 2017) - Howe, Thomas E.; khurram, Syed A.; Hunter, Keith; Martin, Lisette H.C.; Fry, Alastair M.
Abstract: Accurate staging of oral squamous cell carcinoma (oral SCC) is essential. Some clinicians delay diagnostic biopsy until after magnetic resonance imaging (MRI). We retrospectively studied the clinical records and histopathological databases of 58 patients with SCC of the tongue; 39 had biopsy before MRI and 19 afterwards. In the group who had the biopsy first, eight were up-staged, nine were down-staged, and in 22 the T stage was accurate. In those who had MRI first, the corresponding figures were two, six, and 11, respectively. The time between initial biopsy and excision was significantly longer in the MRI group (43 days), than in the biopsy group (16 days) (p < 0.001). Differences in staging between the two groups were not significant. Whether the biopsy was taken before or after MRI does not seem to affect the accuracy of clinical staging, and to delay biopsy until after staging may be unnecessary.